NEW PRODUCT DEVELOPMENT OPPORTUNITIES IN REZEKNE - Dembovska, Iveta; Kovalenoka, Violeta (Journal of Regional Economic and Social Development, 2021)
The tourism industry was one of the fastest growing industries in Latvia until the pandemic was declared in 2020, which brought the entire industry to a halt. Before the pandemic, travel trends were already moving towards the type of experience offered by hostels, and consumer demand had grown in the past years. Moreover, the industry data show that the number of travellers who use hostels is growing. There are several lodging opportunities in Rezekne, but there is no economical option, which would be a hostel. The research aim is to study the theoretical aspects of a new product and analyse the opportunities for the creation of a hostel – a new tourism product in Rezekne. The methods used in the research are monographic, synthesis, statistical analysis methods, and a survey. The research allowed making recommendations for the creation of a new tourism product – a hostel – in Rezekne. The results of the research and survey showed that hostel-level accommodation is needed in Rezekne.